Framing Blackness and Appropriating Monstrosity in Blacula - Isherwood, Laura (FRAME, Journal of Literary Studies, 2026)
This article considers how the Blaxploitation horror classic Blacula (1972) frames and (re)appropriates race, blackness, and monstrosity where genres meet. An analysis of Blacula illustrates how African-American filmmakers and audiences profited from Hollywood’s shifting priorities in the late 1960s as a means to enable black agency, both on the production side and in its powerful (counter) narrative. By creating a complex and sympathetic monster that is simultaneously an agent of black pride, Blacula brings the forgotten history of a marginalized racial community to the silver screen, encourages societal critique, and reflects the shift that took place in African-American identity politics amidst the rise of Black Nationalism in the United States.